Influence Study of Different Anti-Yaw Dampers on EMUs Hunting Instability - WU Huichao; HUO Wenbiao; LU Quan; SHI Junjie (机车电传动)
The influence of different anti-yaw dampers on primary and secondary hunting of CRH3 EMUs was studied. The results showed that T60 anti-yaw damper could restrain carbody primary hunting effectively, but could not restrain bogie secondary hunting. On the contrary, T70 anti-yaw damper could improve bogie secondary hunting immensely, but could not restrain carbody primary hunting. This research result showed that the perfect anti-yaw damper should show smaller stiffness and damping characteristic in low-frequency condition, and bigger stiffness and damping characteristic in high-frequency condition, which would ensure that CRH3 EMUs could adapt to different railway lines, satisfy wheel/rail matching requirement of different worn profile tread and avoid bogie instability alarm or carbody hunting.